Genetic control of silvicultural traits in Balfourodendron riedelianum (ENGL.) ENGL. - Aguiar, B. I.; Freitas, M. L.M.; Tavares, Y. R.; Tambarussi, E. V.; Zanatto, B.; Gandara, F. B.; Paludeto, J. G.Z.; Silva, D. Y.B.O.; Silva, J. R. [UNESP]; Moraes, M. L.T. [UNESP]; Longui, E. L.; Zanata, M.; et al. (De Gruyter, 2020)
The Atlantic Forest has very high levels of biodiversity and is considered one of the most important and threatened biomes in the world. Balfourodendron riedelianum is one of the forest's characteristic tree species that is currently under considered endangered due to timber extraction and forest fragmentation. With the goal of generating information that may contribute to the genetic conservation of B. riedelianum, genetic parameters are estimated for quantitative traits important for silviculture in a provenance and progeny test located in the Experimental Station of Luiz Antônio, São Paulo State, Brazil. The test was established in 1986 and consists of three provenances, from which open-pollinated seeds from 19 seed trees were collected. The following traits were evaluated at 32 years of age: diameter at breast height (DBH), total height (H), stem height (SH), stem straightness (SS), and forking (FOR). The estimates were carried out using the REML/BLUP method. Significant genetic variation among progenies was detected for all traits (except SH) and between provenances for DBH. The coefficient of individual genetic variation (CVgi) ranged from 2.5 to 9.5 %. The mean heritability among progeny (hf2 $h_f^2$) was substantial for DBH (0.44) and FOR (0.36), enabling the selection of families with the highest DBH and lowest FOR for population improvement. Genotypic and phenotypic correlations among traits were also found. We conclude that there is genetic variability in the population that can be exploited in future breeding programs and for the genetic conservation of the species.
Keywords: genetic enhancement; Genetic variation; pau-marfim; provenance and progeny test; tree improvement